2009
DOI: 10.1093/ije/dyp364
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of body mass index and mortality in Bangladesh

Abstract: Underweight (presumably due to malnutrition) is a major determinant of mortality in the rural Bangladeshi population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 31 publications
(35 reference statements)
4
53
0
Order By: Relevance
“…Therefore, we expect that the noise introduced by this weight measuring protocol would not be systematic, and would not result in confounding between genetics and body mass index. A previous study of BMI and mortality on a subset of the same study population was associated with other clinical endpoints in the expected manner [4]. Therefore we have confidence that the BMI we measured accurately captures the BMI of this population.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, we expect that the noise introduced by this weight measuring protocol would not be systematic, and would not result in confounding between genetics and body mass index. A previous study of BMI and mortality on a subset of the same study population was associated with other clinical endpoints in the expected manner [4]. Therefore we have confidence that the BMI we measured accurately captures the BMI of this population.…”
Section: Discussionsupporting
confidence: 52%
“…At the same time the ADA has defined BMI cutoffs for screening for diabetes for Asian Americans, as well as India and other Asian countries ( Japan, China) 37,38 have lowered BMI cut-points to define overweight and obesity based on available data, many would still argue that BMI should only be defined according to overall mortality, particularly when some studies in South Asians have not shown inordinately high mortality at BMI cut-points ‡23 kg/m 2 . 39,40 Time and again, validity of ''health guidelines'' have been questioned because of lack of robust data, particularly in the context of mortality. Could ''less than perfect'' data be enough to make guidelines for improving public health?…”
Section: Ethnicity and Bmi: Contentious Issuesmentioning
confidence: 99%
“…Therefore weight loss (very low BMI) resulting from existing illness may distort the relationship. However, while exploring associations between low BMI and increased mortality in a cohort, Pierce et al did not find any role of possible confounding by co-morbidity (32) . Third, the BDHS 2011 did not collect information on tobacco smoking habits at the individual level (only collected information on second-hand smoke at household level).…”
Section: Discussionmentioning
confidence: 95%